Elucidating the Effects of Reaction Time on the Physicochemical Characterization of Valorized Synthesized Alumina - Bin Mokaizh, A.A. (MDPI, 2022)
Aluminum waste-can management in Malaysia has recently become a serious environmental and public health issue, particularly in metropolitan areas. This has prompted the need to valorize these waste-cans into value-added products using the most economical and environmentally friendly techniques. In this study, the solâgel technique was used to synthesize high-quality alumina from the aluminum waste-cans collected. From this method, the observed peaks of the synthesized alumina were identified as diaspore (Î±-AlO(OH)), boehmite (Î³-AlO(OH)), aluminum oxide, or gamma-alumina (Î³-Al2O3 ) crystalline structure and corundum. The morphological configuration, microstructure, and functional group properties of the synthesized alumina were evaluated. All the synthesized alumina exhibited a non-spherical shape and appeared to have hexagonal-like shape particles. Moreover, the XRD patterns of the synthesized alumina AL-6-30 and AL-12-30 exhibited a small angle (1â10â¦ ) with no XRD peak, which indicated a mesoporous pore structure with no long-range order. The overall results of Î³-alumina synthesized from the aluminum waste-cans showed an optimal condition in producing a highly structured Î³-alumina with excellent surface-area characteristics. The synthesized alumina exhibited stronger and highly crystalline functional characteristics almost comparable with the commercially available brands on the market. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.